Al-Taḥlīl al-Taqābul: Dirāsah Muqāranah bayna al-Lughah al-‘Arabiyyah wa al-Kụriyyah ‘alā Mustawā al-Jumal al-Mubasiṭah wa atsāruha fī Ta’līm al-Lughah al-Kụriyyah - Alvia Putri Prima Sari (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Institut Agama Islam Darullughah Wadda'wah Pasuruan, 2021)
Abstract The aim of this study is to compare the structures of Arabic and Korean sentences in a simple way. The researcher uses a qualitative descriptive method and the type of research is literature review, data collection from primary and secondary data sources. For data analysis, there are two method according to C.C.Fries, namely: 1) descriptive analysis which exposures of the structure between two languages, 2) contrastive analysis which compares the structures of Arabic and Korean sentences to find out the differences, similarities, predictions of learning difficulties in the classroom, selection of methods and subject matter. The result show that there are differences especially in alphabets and the order of sentences .The Korean letters is 40, while Arabic 28,with both having special shapes. It seems that Arabic is flexible, allowing verbs and nouns at beginning of sentences. On the other hand, Korean is fixed, putting the verb after subject and object, because it always puts the noun first in the sentences. Key words: Contrastive Analysis, Structure of Sentences, Arabic, Korean